2018
DOI: 10.1161/circep.117.005592
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Zero X-Ray Ablation for Supraventricular Tachycardias in a Nationwide Multicenter Experience

Abstract: The use of 3-dimensional mapping system completely avoided the use of fluoroscopy in most cases, with very low fluoroscopy time in the remaining and high safety and effectiveness profiles. Achievement of ZFL was predicted by the type of arrhythmia, operator's experience, and patient's age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 19 publications
5
32
0
Order By: Relevance
“…We did not have measures of centers volume or operators’ experience; nevertheless, the procedure and fluoroscopy time were significantly different among the four study groups, whereas fluoroscopy and ablation times were significantly different among the operators. Previous studies have shown that lower operator experience leads to increased fluoroscopy use . In our registry this parameter did not impact the rate of first pass PV isolation.…”
Section: Discussionmentioning
confidence: 48%
“…We did not have measures of centers volume or operators’ experience; nevertheless, the procedure and fluoroscopy time were significantly different among the four study groups, whereas fluoroscopy and ablation times were significantly different among the operators. Previous studies have shown that lower operator experience leads to increased fluoroscopy use . In our registry this parameter did not impact the rate of first pass PV isolation.…”
Section: Discussionmentioning
confidence: 48%
“…27 In their study, Raju et al demonstrated that general anaesthesia, transoesophageal echocardiography and contactforce mapping catheters may all facilitate a minimised fluoroscopic approach among AF ablation patients. 28 In this population, complete zero-fluoroscopy was possible in cases with patent foramen ovale (PFO), which was documented in 36% of patients. 28 In 2016, we published a study of 442 consecutive patients who were referred for radiofrequency catheter ablation during a 5-year period (2009-2013).…”
mentioning
confidence: 94%
“…28 In this population, complete zero-fluoroscopy was possible in cases with patent foramen ovale (PFO), which was documented in 36% of patients. 28 In 2016, we published a study of 442 consecutive patients who were referred for radiofrequency catheter ablation during a 5-year period (2009-2013). 12 The patients were included in a retrospective observational study, where the first 145 patients (group 1) were treated only under fluoroscopic guidance; the other 297 patients (group 2) were treated with a non-conventional mapping system.…”
mentioning
confidence: 94%
“…However, the widespread use of non-fluoroscopic mapping systems has introduced the possibility of performing this procedure without the need for fluoroscopy, without affecting the efficacy and safety of the procedure. [31][32][33] In particular, the most used electroanatomical mapping system are currently Carto (Biosense Webster, Johnson and Johnson, USA), EnSite Precision (Abbott, USA) and Rhythmia (Boston Scientific, USA). All these systems are characterized in their updated version by the ability to perform a magnetic and electrical three-dimensional (3D) anatomical reconstruction of the cardiac chambers and real-time visualization of the catheters.…”
Section: Future Perspectivesmentioning
confidence: 99%